Predictors of Childhood Intractable Epilepsy- A Retrospective Study in A Tertiary Care Hospital (Bangladesh Journal of Child Health, 2010)
Objective: To study the predictors of intractable childhood epilepsy and to comparethe predictors of outcome in early and late onset childhood epilepsy.Design: Retrospective study.Study place: Child Development and Neurology Unit in the Department of Paediatricsof Bangabandhu Sheikh Mujib Medical University (BSMMU).Study period: January 2004 to December 2005.Subjects: Children with epilepsy of 1 month to 15 years of age who attended theepilepsy clinic.Results: The predictors of outcome of childhood epilepsy were analyzed. Accordingto outcome there were two groups, well- controlled group (seizure free for more than 6months) and intractable epilepsy ( one or more seizures per month over a period of 6months). The predictors of early and late onset childhood epilepsy were also compared.Total 73 cases were studied. Out of them 38 patients had early onset epilepsy (lessthan one year) and 35 had late onset epilepsy (more than one year). Median age ofonset of early and late onset of childhood epilepsy group was 3.5 months and 60months respectively. Male and female ratio was 1.53:1 and 0.94:1 in early and lateonset group respectively. Major seizure type was tonic-clonic seizure in 57.9% and77.1% patients of early and late onset group respectively. In this study, 27 (77.1%)patients of late onset and 5(13.2%) patients of early onset group achieved seizureremission. Independent predictors of intractable childhood epilepsy were finally found.Conclusion: In this study symptomatic epilepsy, myoclonic seizure, initial highfrequency of seizure, infantile spasm, neonatal seizures and birth asphyxia weresignificantly higher among early onset group than in late onset group. Early onset ofseizure, myoclonic seizure, initial high frequency of seizure (≥1 seizure/day),symptomatic etiology, neonatal seizure and microcephaly were found independentpredictors of intractable epilepsy.Key words: Early onset; late onset; intractable seizures.DOI: 10.3329/bjch.v33i1.5669Bangladesh Journal of Child Health 2009; Vol.33(1): 6-15